Comparative in Vitro Study Between the Visibility of the Caries Lesion and the Optic Density of Proximal Surfaces in Deciduos Molars - Tania DHREMER; Márcia Cançado FIGUEIREDO; Zini BÁRBARA; Mircelei Saldanha SAMPAIO; Vanessa Constant BARRETO (Association of Support to Oral Health Research (APESB), 2006)
Objective: This report uses the indirect digital image program "DentScan-DentView"®, in order to compare averages of optical density in carious lesion with visible activity and inactivity in healthy tissue of primary molars all done in vitro. Method: The sample of 193 proximal faces in primary molars was visually analyzed, x-rayed and scanned. It was used 't' of paired Student test and ANOVA with Tuckey test for statistical analysis. Results: The average of optical density in rigid tissues (enamel and dentine in the control group), were always higher than in tissues with carious lesion diagnoses using visual and tactile clinical exams in vitro, in the same teeth. Conclusion: It was concluded that the average of enamel optical density is significantly over the level p<0.0001 compared to dentine and tissues with proximal carious lesion. The enamel optical density seems to decrease with in increase of proximal carious severity.